Construction of the School Physical Environment Standardized Features Tool - Salih, hewa; Khalifa, mohammed (Iraqi National Journal of Nursing Specialties, 2013)
Objective: A descriptive design, using the methodological approach, is carried throughout the presentstudy from April 1st 2012 to May 20th 2013 to construct the school physical environment standardizedfeatures tool.Methodology: An instrument of (141) item is constructed for the purpose of the study. A purposivesample of (44) school; (22) public and (22) private ones is selected. Content Validity of the instrument isdetermined through the use of panel of (11) expert who are specialists in Community Health Nursing andCommunity Medicine. Internal consistency reliability, using the split-half technique, is employed throughthe computation of Cronbach alpha correlation coefficient of (0.93) for internal scale. Data were collectedthrough the use of the instrument and the schools' visits as means of data collection. Data are analyzedthrough the application of the inferential statistical data analysis procedure of simple Pearson’scorrelation coefficient and factor analysis (principle component) method.Results: Findings of the study reveal that the features are presented, post their rearrangement, under fivefactors that include school services, emergency and school sanitation, food and protection services, safeschool environment, and school environment. So, the new tool can be structured, tested and used asguide for new investigations. Such presentation of factors reflects the actual model by which the school'sphysical environment features can be considered as essential elements for future evaluation through theutilization of the constructed tool.Recommendations: The study recommends that the new discovered tool can be used as measure forfuture work, and further studies can be carried out on large sample size and nation-wide base.